Characterization of immunosuppression of genotype A2dB1 variant infectious bursal disease virus isolated in Malaysia using specific pathogen-free and commercial broiler chickens - Paniz Zarghami Dastjerdi; Mohd Hair Bejo; Nor Yasmin Abd Rahaman; Abdullahi Abdullahi Raji; Roikhwan Soontravanich; Shen Rong Tai; Abdul Rahman Omar (Veterinary World)
Background and Aim: Infectious bursal disease (IBD) is an immunosuppressive disease caused by the IBD virus (IBDV), which adversely affects poultry vaccination programs. The novel variant IBDV (nvIBDV) has recently emerged in various regions, including Malaysia, raising concerns about its immunosuppressive potential and impact on Newcastle disease (ND) vaccination. This study aimed to investigate the immunosuppressive effects of the Malaysian nvIBDV strain (UPM1432/2019) in specific-pathogen-free (SPF) and broiler chickens and evaluate its influence on ND vaccine efficacy.